The role of religion in modern Russian nation building - O. V. Kuropatkina (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2018)
This article examines the state of religion in modern Russia, religious and ethnic groups, as well as forms of consolidation religious communities, contributing to the nation building.